Evaluation of Tamarindus indica as novel feed resource in tropical animal production and management - Sikiru, A. B.; Makinde, O.J.; Opoola, E.; Uyanga, V. A. (Nigerian Journal of Animal Science, 2023)
Unconventional feed resource for livestock production in the tropics has been identified as a way of reducing the challenges of shortage and high – cost of conventional feed resources because of the competition between man and animal. Therefore, nutritional value of Tamarindus indica whole fruit, hulls and seeds was investigated in this study. Determination of proximate components using standard methods was carried out on the samples separately and thereafter subjected to in-vitro digestibility evaluation. Proximate analysis results showed that the concentrations of chemical components in whole fruit, hulls and seeds respectively as determined on dry matter basis in percentage (%) were: moisture (13.39; 12.25; 4.60), ash (7.18; 5.50; 7.15), crude protein (13.75; 9.12; 22.60), crude fibre (15.50; 15.00; 10.00), ether extract (9.25; 7.72; 9.50) and metabolizable energy (4324; 4084; 4633 Kcal/Kg). This indicated that crude protein content were significantly higher (P<0.05) in the seed as compared to the whole fruit and hulls while the Tamarindus fruit hull contained significantly lower (P < 0.05) values components measured. The results of the in-vitro nutrients digestibility showed that crude protein, crude fibre and ash digestibilities respectively were significantly higher (P<0.05) for tamarind seeds (94.96 %, 53.41 %, and 64.69 %) as compared to the whole fruit and hulls which were similar (P>0.05). From the results, it was concluded that the seed of Tamarindus indica is a potential unconventional protein source for livestock production in the tropics and its in-vivo evaluation is hereby recommended prior to its use as a novel feed resource for commercial animal production.